2018
DOI: 10.1186/s12936-017-2150-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and household attributes may not necessarily influence malaria: evidence from a cross sectional study of households in an urban slum setting of Chennai, India

Abstract: BackgroundHousehold and environmental factors are reported to influence the malaria endemicity of a place. Hence, a careful assessment of these factors would, potentially help in locating the possible areas under risk to plan and adopt the most suitable and appropriate malaria control strategies.MethodsA cross-sectional household survey was carried out in the study site, Besant Nagar, Chennai, through random sampling method from February 2014 to February 2015. A structured interviewer-administered questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Similar findings have also been reported by many other earlier studies, even though using different proxies, i.e. including the number of people in the house [ 15 , 26 , 31 , 40 ] and the number of people per room [ 42 ]. This could be because large families are more likely to have younger children in the family which are a high risk group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings have also been reported by many other earlier studies, even though using different proxies, i.e. including the number of people in the house [ 15 , 26 , 31 , 40 ] and the number of people per room [ 42 ]. This could be because large families are more likely to have younger children in the family which are a high risk group.…”
Section: Discussionsupporting
confidence: 90%
“…The division of labour as a result of gender roles may play a significant part in determining exposure to mosquitoes [ 33 ]. Many studies reported a similar risk for both genders [ 15 , 16 , 34 ]. However, some studies reported females to have a higher risk because they are primarily responsible for many household activities [ 35 ]and they start their day early and before dawn to perform household chores [ 36 ], but others reported males having greater occupation risk of contracting malaria [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found no association between malaria prevalence and educational level, marital status and occupation of the study subjects. These sociodemographic factors were similarly reported in several studies [14,15] not influencing malaria prevalence.…”
Section: Discussionsupporting
confidence: 86%
“…Due to a lack of healthcare facilities, many have pre-existing medical conditions putting them at high risk of dying or developing serious complications if they get sick with the virus. (Thomas et al, 2018) The social isolation measure is devastating for the many slum dwellers where physical space is scarce and many rely on daily wage labor for survival. (Marimuthu, 2016) The general hand-to-mouth existence of the people has only become worse with the effect of COVID -19.…”
Section: Effect Of Covid-19 In the Slums Of Chennaimentioning
confidence: 99%